2022
DOI: 10.1038/s41598-022-18322-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the toxic effect of ZIF-8 and ZIF-L on the colonization and decomposition of shaded outdoor mice carrions by arthropods

Abstract: Metal–organic frameworks (MOFs) are promising materials for several applications. Thus, they have been intensively reported and commercialized by several international companies. However, little is known about the fate and risk of MOFs to living organisms. Here, the toxic effect of two Zinc (Zn)-based MOFs; zeolitic imidazolate frameworks (ZIF-8) and leaf-like ZIF (ZIF-L), was tested to investigate the impact of the postmortem period of mice carrions and arthropods which found in decomposing carrions. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…ZIF-8 demonstrated its high activity in photocatalytic reactions like CO 2 reduction, E. coli inactivation as well as antibacterial capability with high structure stability. ,, The toxicity of ZIF-8 is very low and has been used for bioapplications. , Thus, ZIF-8 NPs were selected as the functional heterophases for air filtration/purification and antibacterial applications. For a smooth ZIF-8 electrospray, the ZIF-8 NPs are required to be predispersed in the solvent, which is also compatible with the HFP solvent that dissolves PLA/PHBR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ZIF-8 demonstrated its high activity in photocatalytic reactions like CO 2 reduction, E. coli inactivation as well as antibacterial capability with high structure stability. ,, The toxicity of ZIF-8 is very low and has been used for bioapplications. , Thus, ZIF-8 NPs were selected as the functional heterophases for air filtration/purification and antibacterial applications. For a smooth ZIF-8 electrospray, the ZIF-8 NPs are required to be predispersed in the solvent, which is also compatible with the HFP solvent that dissolves PLA/PHBR.…”
Section: Resultsmentioning
confidence: 99%
“…42,62,63 The toxicity of ZIF-8 is very low and has been used for bioapplications. 64,65 Thus, ZIF-8 NPs were selected as the functional heterophases for air filtration/purification and antibacterial applications. For a smooth ZIF-8 electrospray, the ZIF-8 NPs are required to be predispersed in the solvent, which is also compatible with the HFP solvent that dissolves PLA/PHBR.…”
Section: Synthesis Of Phb-di-poly(dla-cl) Xmentioning
confidence: 99%
“…Thus, ZIF-8 was widely used for biomedical applications [192] including gene delivery [193]. However, our recent study showed the transfer of the metal ions into the environment that caused a significant effect on the colonization and decomposition of shaded outdoor mice carrions by arthropods [194].…”
Section: Metal-organic Framework (Mofs)mentioning
confidence: 99%
“…ZIF-L was prepared via a one-pot method. 53,54 Typically, Zn (NO 3 ) 2 •6H 2 O (5 mmol, 1.5 g) was dispersed in TOCNF (100 mL, 1.5 wt.%) using an Ultra Turrax (IKA) at 15 000 rpm for one hour. NaOH (10 mL, one mmol) was then added dropwise with stirring.…”
Section: Ink Preparation and 3d Printingmentioning
confidence: 99%